The Chinese Migrant Worker in Indonesia: The Local and Migrant Workers Context - Maksum, Ali; Sahide, Ahmad (Jurnal Ilmiah Peuradeun, 2019)
Based on empirical findings, this article concludes that the influx of Chinese migrant workers is a serious threat against Indonesian local and migrant workers in the overseas, amidst the high number of unemployment. The local and migrant workers have struggled to seek for a better job under uncertain situation in Indonesia. The Indonesian government attempts to create more job vacancies, yet the government has welcomed more migrant workers especially from China. Furthermore, Indonesian migrant workers are also recognized as the highest contributor for Indonesian remittance for many years. The influx of Chinese migrant workers blatantly hit both Indonesian local and migrant workers. In addition, this was a humiliation against Indonesian workers, which have struggled to migrate overseas through illegal and very risky ways. Conversely, a large number of Chinese migrant workers have been deployed in various projects, which basically can be handled by local workers. The arrival of Chinese migrant workers, of course, became a controversial issue especially among Indonesian local and migrant workers, who have faced difficult situation such as exploitation, humiliation, and contract abuses. This is a qualitative research enriched with semi-structured interviews with some key respondents specifically those who have experiences and expertise on migrant workers issues.